Comprehensive numerical study of the effect of nanoparticle additives on the cutting transport performance in horizontal boreholes. Issue 1 (26th November 2020) - Minakov, Andrey V; Mikhienkova, Evgeniya I; Neverov, Alexander L; Rudyak, Valery Ya
Abstract: The results of a numerical study of the effect of nanoparticle additives in the drilling fluid on the efficiency of cuttings removal from a horizontal well are presented. The rheological parameters of drilling fluids with nanoparticles (NPs) were set from the experiment. The SiO2 and Al2 O3 NPs were used. The concentration of NPs in the drilling fluids varied from 0.25 to 2 wt%, while their average diameter ranged from 5 to 50 nm. The Eulerian granular media approach was used to simulate the cutting transport from the borehole. The numerical model was tested in detail on well-known experimental data on sand suspension flow in a round pipe. A good agreement with the experiment was obtained. A systematic computational study of the influence of several parameters on the efficiency of removing cuttings from the well was carried out. These parameters included the well's inclination angle from the vertical direction, the speed of rotation of the drill pipe, the flow rate of the drilling fluid, and the concentration, size, and composition of nanoparticles. It is shown that the 2 wt% concentration of nanoparticles in the drilling fluid results in a 2.7-fold increase in the cutting transport performance for horizontal boreholes. The positive effect of adding nanoparticles to the drilling fluid is enhanced with decreasing nanoparticle size. Graphical Abstract: